Running performance: The importance of selecting the right gear - Stefanyshyn, D. J. (International Calgary Running Symposium, August 14-17, 2014, 2014)
When running, the foot acts as a lever, rotating about the ankle joint. As the triceps surae muscles contract and lift the calcaneus during pushoff, the talus rotates about the tibia causing the metatarsals and phalanges to push against the ground and propel the runner. The ratio of the distance (or lever arm) between the Achilles tendon and the ankle joint and the distance (or lever arm) between the ankle joint and the metatarsophalangeal joint is often referred to as a gearing ratio during running. This gearing ratio is typically genetically determined and it has been found that runners with a higher gear ratio (smaller distance between the Achilles tendon and ankle joint) have better running economy than runners with a lower gearing ratio. Thus it appears that increasing the gearing ratio may directly improve performance. Since the Achilles tendon lever arm is defined anatomically, the only way to modify the gearing ratio is to manipulate the lever arm of the foot. Manipulating the longitudinal bending stiffness of running shoes can modify the lever arm of the foot; increased bending stiffness increases the lever arm. We have found that increasing the shoe bending stiffness compared to traditional stiffness values can increase running economy. However, excessively increasing the stiffness is detrimental to running economy. Thus it is important to properly select the appropriate shoe bending stiffness, to optimize the lever arm of the foot, and select the right gear for maximizing running economy.